Pemantauan Minum Obat dengan Menggunakan Media Komunikasi Digital pada Pasien Tuberculosis - Ristinawati Ristinawati; I Made Kariasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to explore the effectiveness of modifying drug-taking control using digital communication media on Tuberculosis survivors. The research method used is a literature review by searching five databases. Namely, Google Scholar, Clinical Key, EbscoHost, and Pubmed, using the keywords